A total systems analysis of AM Cleofe Prints - Briones, Ralph Carlo E.; Castaneda, Charmaine F.; Castillo, Joyce S.; Dela Cruz, Tazha Rachel T.
AM Cleofe Prints is a small scale printing company located along Visayas Avenue, Quezon City. It provides design, layout and print services to a broad range of local customers from various institutions.The company has been in operation since 1984 under the management of its owner and other family members.This study, entitled Total Systems Analysis of AM Cleofe Prints, is an analysis of AM Cleofe's entire operations. The organizational profile and background sections focus on the nature of AM Cleofe's business operation. These. parts tackle the products that they offer to their market as well as their strategy of delivering their products to their customers. Also tackled here is the description and mapping of the organization's structure like the organizational tree, workforce profile, key suppliers and partners, facilities and equipments, and key company rules and policies regarding day-to-day operation. The Define Phase section establishes the goals of this project. This section establishes the direction of the study by focusing on improving the current state of the company which can be achieved by improving the balance between their capacity and volume of demand that they receive. The goal of this study is to minimize the negative effects of the stated imbalance in the system such as overtime cost and late delivery of orders. The Measure Phase section is about establishing the current state of the system. The problems experienced by the company are quantified here to assess its magnitude on the company's operation. This section also establishes base values of Key Performance Indicators of the system. The base value will serve as the basis of evaluation if improvements are really achieved at the end of the study. The Analysis Phase section tackles the discussion of possible causes resulting to the disparity between the current situation of the company and their goals. Several tools are used such as Causal Systems Archetypes, Cause and Effect Analysis, Value Stream Mapping, and Gap Analysis to identify the root cause of the current system's problem. The findings in this phase suggest that the main causes of the problem in the current state of operation are insufficient capacity in the printing operation and lack of formal production scheduling technique. The Optimization and Improvement Phase section describes the process of generating solutions to the identified root causes. With thorough analysis and discussion, this study is able to provide 3 key outputs that will help the company in addressing their current situation. A computer simulation is created that will allow the company to identify the most optimal working hours in relation to the demand. A Knapsack linear program is also formulated that will aid the production manager in creating the weekly production schedule. Finally, a database is also created to allow the management to keep records about their customers and their transactions which will enable the management to accurately forecast future changes in the demand level. This will enable them to adjust accordingly and keep their business operating at the most optimal level. Finally, the Verification and Control Phase section discusses the expected benefits that the company will achieve after implementing the suggested improvements. This section aims to convince the management that the benefit brought by the changes will outweigh the cost of its implementation. This section also discusses other opportunities for improvement that are not covered by the study so that the company can still experience progress even after the duration of this study.